O escutar: confissões sobre sexualidade - Aguiar, Janaína da Silva (2011)
Introduction: Over the life the body ages, evolving into the following stages: child, adolescent, adult and old age. A good part of the population reaches old age, this step carries a bag full of good and bad experiences. Will this age group continues to experience good feelings, even berating the company? So what is the meaning of sexuality for them? Purpose of research: Understanding the meaning of sexuality for individuals over 70 years. Methods: We studied five patients (three females and two males), with the following criteria: over 70 years, therapy sessions, resident in the west and the cognitive factor preserved. Being held open interviews with a few questions, ending with an individual analysis and overall compared with the theoretical support. Analysis: The majority of respondents reported that sexuality is never gone, at the point of view, and theoretical support of sexuality begins with the emotional, affective and ends with sex. Already a minority had a sexual experience with positives, so do not know whether express or fall short of these experiences. Final Thoughts: When interviewed individuals over 70 years the answers are close to the theoretical, but when the same questions were proposed for adolescents and adults do not know the difference between sex and sexuality